Character Building in Students through “Rumi Sang Pemimpi”: A Digital Book Approach - Harmawati, Yuni; Sapriya, Sapriya; Abdulkarim, Aim; Bestari, Prayoga (Universitas Islam Negeri Raden Intan Lampung, 2024)
Technological advancements have transformed the learning landscape for students in schools. Unlike the past, where discussions were confined to the classroom, today's students engage in digital discussions through platforms like Zoom Meetings, Google Classroom, or school-provided eLearning. The impact of technology on students is twofold, presenting both positive and negative aspects. In an effort to enhance student learning and character development, researchers have created a non-text digital book on citizenship education. Utilizing Borg and Gall's research methodology, data collection involved questionnaires, focus group discussions, interviews, and observations. The research findings demonstrate the viability of digital non-text civics education books, indicating their applicability in junior high schools to bolster students' hard-working character. Significant differences in the aspect of hard work were observed between the experimental and control groups in various tests. In conclusion, digital books with the theme ”Rumi Sang Pemimpi” (in English: ”Rumi the Dreamer”) prove effective in strengthening students' character, particularly their hard-working traits. The researcher recommends further exploration of characters in the digital book related to digital citizenship.